Predictability of formulae for intraocular lens power calculation according to the age of implantation in paediatric cataract. Issue 1 (31st March 2018) - Lee, Byung Joo; Lee, Sang-Mok; Kim, Jeong Hun; Yu, Young Suk
Abstract : Aims: To analyse the predictability of diverse intraocular lens (IOL) power calculation formulae in paediatric patients with congenital cataract. Methods: The medical records of patients who underwent cataract surgery and posterior chamber IOL implantation (in-the-bag) for congenital cataract before 17 years of age were reviewed retrospectively. Target refractions calculated by Sanders-Retzlaff-Kraff (SRK)/II, SRK/T and Hoffer-Q formulae were compared with the actual refraction. Patients were subgroup according to the age at IOL implantation (age group 0–24 months, 25–60 months, 61–120 months, 121–203 months), and we compared mean prediction error (PE) and mean absolute error (AE) for each formula. Corrected AE was obtained by linear regression analysis. Results: Totally 481 eyes were included in the final analysis. Both SRK/II and SRK/T yielded the lowest mean AE in the age group 0–24 months and SRK/II yielded the lowest mean AE in the age group 25–60 months. For every formula, the mean PE was positive during the first five years of age, which converged to zero according to age as IOL implantation increases. The tendency for immediate postoperative overcorrection in younger patients (<6 years) could be improved by corrected formulae based on the linear regression equation. Conclusions: Patients with congenital cataract who underwent IOL implantation within 5 years of age showed higher AE than the older ones did. Among the three formulae evaluated, SRK/II consistently provided the best predictive result in these patients. For patients aged >10 years, all three formulae showed favourable predictive abilities.